Isolation of pancreatic microbiota from cystic precursors of pancreatic cancer with intracellular growth and DNA damaging properties. (1st January 2021) - Halimi, Asif; Gabarrini, Giorgio; Sobkowiak, Michał Jacek; Ateeb, Zeeshan; Davanian, Haleh; Gaiser, Rogier Aäron; Arnelo, Urban; Valente, Roberto; Wong, Alicia Y.W.; Moro, Carlos Fernández; Del Chiaro, Marco; Özenci, Volkan; et al.
ABSTRACT: Emerging research suggests gut microbiome may play a role in pancreatic cancer initiation and progression, but cultivation of the cancer microbiome remains challenging. This pilot study aims to investigate the possibility to cultivate pancreatic microbiome from pancreatic cystic lesions associated with invasive cancer. Intra-operatively acquired pancreatic cyst fluid samples showed culture-positivity mainly in the intraductal papillary mucinous neoplasm (IPMN) group of lesions. MALDI-TOF MS profiling analysis shows Gammaproteobacteria and Bacilli dominate among individual bacteria isolates. Among cultivated bacteria, Gammaproteobacteria, particularly Klebsiella pneumoniae, but also Granulicatella adiacens and Enterococcus faecalis, demonstrate consistent pathogenic properties in pancreatic cell lines tested in ex vivo co-culture models. Pathogenic properties include intracellular survival capability, cell death induction, or causing DNA double-strand breaks in the surviving cells resembling genotoxic effects. This study provides new insights into the role of the pancreatic microbiota in the intriguing link between pancreatic cystic lesions and cancer.